Pregraduation online curriculum delivery of internal medicine course during the COVID-19 pandemic: Experience of a medical college in Saudi Arabia - Salman Aljarallah; Mohammed Bedaiwi; Rashed Alrashed; Mohammed A Omair; Mona Soliman; Assim A Alfadda (Wolters Kluwer Medknow Publications, 2021)
Background: The COVID-19 pandemic has challenged medical education and resulted in a rapid and unexpected global shift toward online education. The study presents the experience of the College of Medicine of King Saud University in delivering a comprehensive internal medicine course for final-year medical students, which includes the implementation of novel methods of assessment. Methods: A 2-week revision of the internal medicine course was conducted for 70 pregraduation medical students. Lectures and focused case-based tutorials were conducted online. Novel assessment methods included brief written essays summarizing the tutorials, open-book short-answer question (SAQ) examination, and a virtual standardized oral examination (vSOE). A questionnaire was sent to the students (n = 70) on the contents of the course, clarity of objectives, duration, and online platform. Results: The response rate was 99.3%. Students scored higher in the SAQs compared with traditional multiple-choice tests (mean score: 92.3% vs. 69.8%). The vSOE was efficient, and grades were comparable to traditional objective structured clinical examination. The majority of students (93%) reported the scientific content as good or excellent, whereas approximately 30% found the course goals lacked a clear description. The majority (76%) found the course length appropriate, and 94% reported the online platform installation and operation easy or very easy. Conclusions: The comprehensive online internal medicine course was successfully delivered to pregraduation students. Innovative online examination methods can be a reasonable alternative in the case of lockdown. This modality of teaching and assessment was considered useful and met the expectations of students.